Quantitative Study on the Chemical Solution Deposition of Zinc Oxysulfide. (21st November 2015) - Reinisch, Michael; Perkins, Craig L.; Steirer, K. Xerxes
Abstract : Zinc Oxysulfide (ZnOS) has demonstrated potential in the last decade to replace CdS as a buffer layer material since it is a wide-band-gap semiconductor with performance advantages over CdS (Eg = 2.4 eV) in the near UV-range for solar energy conversion. However, questions remain on the growth mechanisms of chemical bath deposited ZnOS. In this study, a detailed model is employed to calculate solubility diagrams that describe simple conditions for complex speciation control using only ammonium hydroxide without additional base. For these conditions, ZnOS is deposited via aqueous solution deposition on a quartz crystal microbalance in a continuous flow cell. Data is used to analyze the growth rate dependence on temperature and also to elucidate the effects of dimethylsulfoxide (DMSO) when used as a co-solvent. Activation energies (EA ) of ZnOS are calculated for different flow rates and solution compositions. The measured EA relationships are affected by changes in the primary growth mechanism when DMSO is included.